Jugando, identifico delante - detrás de - Shuan Lazaro, Silvia Diana (2018)
This project called Playing, I identify in front of and behind, aims to develop spatial thinking in children, as well as various competencies related to geometry and spatial reasoning are important elements of early learning of mathematics, but they are often overlooked, because early childhood teachers do not recognize spatial thinking in children's play and miss opportunities to develop and expand children's thinking. The first chapter is intended for the approach of planning a Learning Session. The second chapter sets out the rationale for the area of Mathematics, according to the National Curriculum of Basic Education (CNEB); Theoretical Sustentum takes into account the development of math skills in early-level children. In the third chapter, the Pedagogical Sustenment is presented concerning psychopedagic principles, pedagogical processes that develop in a learning session. Finally, early-level children are sought to develop the basic competencies to successfully consolidate a progressive process in their learning from a transcendental area such as Mathematics.